PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN CUSTOMER SERVICE DI MATAHARI DEPARTEMENT STORE METROPOLITAN MALL BEKASI - Alfi Nur Arafah; Jamaludin Khalid (Panorama Nusantara, 2022)
Studying consumer satisfaction at Matahari Department Store Metropolitan Mall Bekasi is the primary objective in this study. Matahari Department Store Metropolitan Mall Bekasi customers were surveyed as part of the study's 100-person sample. Participants in the research were asked to fill out questionnaires. Respondents have to have made a purchase at Matahari Metropolitan Mall Bekasi using purposive sampling. For the most part, this study relied on conventional hypothesis testing (Normality Test, Heteroscedasticity Test, Multicollinearity Test and Linearity Test). The quality of a company's products and services are inextricably connected, yet there is no connection between customer pleasure and marketing efforts. A significant correlation exists between customer satisfaction and product, service, and advertising quality according to the f test results. Almost two-thirds of the variance in product quality may be explained by the coefficient of determination. Keywords: Product Quality, Service Quality, Promotion